2017
DOI: 10.1186/s12940-017-0324-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extreme weather events and climate change for health and social care systems

Abstract: This review, commissioned by the Research Councils UK Living With Environmental Change (LWEC) programme, concerns research on the impacts on health and social care systems in the United Kingdom of extreme weather events, under conditions of climate change. Extreme weather events considered include heatwaves, coldwaves and flooding. Using a structured review method, we consider evidence regarding the currently observed and anticipated future impacts of extreme weather on health and social care systems and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 104 publications
(97 reference statements)
1
102
1
3
Order By: Relevance
“…At present, research on the association between ambient temperature and human health has mainly focused on the effects of extreme heat weather, and public health plans have implemented policies and interventions designed almost exclusively for heat wave [5,6]. However, a cold spell risk is generally ignored compared with previous studies focusing on heat waves [7,8].…”
Section: Of 12mentioning
confidence: 99%
“…At present, research on the association between ambient temperature and human health has mainly focused on the effects of extreme heat weather, and public health plans have implemented policies and interventions designed almost exclusively for heat wave [5,6]. However, a cold spell risk is generally ignored compared with previous studies focusing on heat waves [7,8].…”
Section: Of 12mentioning
confidence: 99%
“…In recent years, extreme climate changes have caused wide attention because it has significant impacts on everyday life (Curtis et al, ; Easterling et al, ; Hashim & Hashim, ; Zhang et al, ). During the recent global warming hiatus, Seneviratne et al () found a continued increase (no pause) in hot extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive literature reviews have been recently performed to assess the current state of the science regarding climate change 2,8 , associated adverse health outcomes from weather-related disasters 15,16,38,39,66,67 , public health disaster research 68,69 , and disaster epidemiology 70 . However, we are unaware of any systematic literature review of the intersections between climate change, adverse weather-related disasters, and population health adaptation strategies.…”
Section: Methodsmentioning
confidence: 99%